Efforts to Prevent Stunting Through Fun Cooking Activities in Kindergarten Group A - Umami, Riza; Saputri, Senny Weyara Dienda; Widiastuti, Reski Yulina (Universitas Pendidikan Ganesha, 2024)
Stunting prevention efforts are generally carried out through integrated health service post activities, exclusive breastfeeding, increasing environmental capacity, economy, and community welfare, and health care. This study aims to analyze the level of validity, effectiveness, and practicality of fun cooking activities as one of the efforts to prevent stunting in group A children in kindergarten. This type of research is development research using the ADDIE model. The subjects of this study were 36 children in group A of Al Hikmah Kindergarten. Data collection in this study was carried out using interview, observation, and documentation techniques. Data analysis techniques include validity tests, effectiveness tests, and practicality tests. The results of the study showed that the level of children's recognition of healthy and nutritious food was still lacking. Fun cooking activities carried out twice were a solution in introducing healthy food to children. On the first day, children learned about local food, its nutrition, and benefits; on day two, they processed it. This activity aims to boost preference for local food and reduce unhealthy eating, with validation results confirming it is highly feasible to implement. In terms of effectiveness and practicality, fun cooking activities received a very effective and very practical assessment based on evaluations from educators and parents. This shows that fun cooking activities can be an innovative learning method in supporting efforts to prevent stunting in early childhood. The latest information in this study can have implications for increasing efforts to prevent stunting in early childhood.